Digital Video Project: An Authentic Assessment to Assess Students’ Speaking Skills - Sumardi Sumardi; Rohmatul ‘Adzima; Andik Nur Wijaya (Indonesian Journal of EFL and Linguistics, 2020)
This study was conducted to explore the use of digital video projects and to describe students' perceptions towards digital video project in the speaking assessment. The recorded students' speaking performances were assessed based on a speaking rubric that was adopted and modified to meet the requirements in authentic assessment using digital video projects. The criteria focused on three aspects, they are content, delivery, and creativity. This research involved 25 private university students from non-English departments who joined the English course at Universitas Slamet Riyadi Surakarta. The study utilized a content analysis method with a qualitative approach. The data were collected through the analysis of students' speaking rubric to explore the use of digital video project in speaking assessment and open-ended questionnaire to know the students' perception towards digital video project in the speaking assessment. In completing the project, the students follow four steps: starting the project, developing the project, reporting to the class, and assessing the project. The findings showed that digital video project helps learners to improve their ability to create a right introduction, keep their voice volume and expression, and promote their creativity to make interesting videos. The implication of the research is by employing the digital video project they create, students learn to speak and explore their ideas.